Evaluation of engine efficiency, emissions and load range of a PPC concept engine, with higher octane and alkylate gasoline. (1st September 2020) - Dimitrakopoulos, Nikolaos; Tunér, Martin
Highlights: PPC engine's performance is evaluated with RON90 gasoline and alkylate gasoline. The unoptimized PPC engine with RON90 fuel can operate between 5 and 18 bar IMEPg. Similar brake efficiency (~41%) as in diesel operation but improved soot emissions. Gasoline with ethanol has better PM emissions compared to fuel with no aromatics. Abstract: Gasoline Compression Ignition research has shown that it can provide diesel like engine efficiency while maintaining gasoline like exhaust emissions. While research has shown that lower octane fuels might be good for that, they are also not available now. A good compromise for that would be the use of higher octane gasoline which is available in most places. For this study, experiments were performed under Partially Premixed Combustion (PPC) conditions with RON 90 gasoline, in a 2 L multi-cylinder diesel engine which complies with Euro 6 emissions standards. The aim is to evaluate the efficiency, the emissions and the achievable load in terms of minimum and maximum at three different speeds, 1200, 1800 2400 rpm and with two different RON 90 gasolines and the standard diesel engine hardware. The two fuels were a regular pump gasoline and an alkylate gasoline, which was chosen to represent a pathway to a renewable fuel. Results show that the minimum load is around 5 bar IMEPg, limited by high COV (coefficient of variation) values and high air intake temperature, while the maximum load reaches 18 bar IMEPg, limited by lambda value, pressure and mechanical limitations. While efficiency is similar between the two fuels with a brake value of around 40%, at higher loads the alkylate fuel produces higher amounts of soot while the regular gasoline has higher carbon monoxide at low loads. Finally, an energy balance comparison between the two gasolines and diesel is made, showing improved efficiency and soot emissions under PPC.